Análise econômico-financeira da empresa PETROBRÁS no período de 2005 a 2015 - Neves, Yara [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The objective of this bachelor thesis is to analyze the recent case of the Brazilian company Petrobrás, from the point of view of the financial statements, based on financial and economic indexes, which evaluate a company's financial health. Along with the indexes, it will be also analyzed the Company's history, and the Brazilian and international economic backgrounds in which the facts occurred. Thereby, it will be possible to better understand the variations in the balance sheet, as well as in the statement of income, that occurred from 2005 until 2015, considering, in addition: the Brazilian economic growth, the 2009's international crisis, the recovery of the Brazilian economy, and the political and economic recession that took place in Brazil since the end of 2014

O presente trabalho de monografia tem como objetivo analisar o caso recente da Petrobrás sob o ponto de vista das demonstrações financeiras, tendo como base os índices financeiros e econômicos, que avaliam a saúde de uma empresa. Acompanhado aos índices, será analisada também a história da Companhia, e o cenário econômico brasileiro e internacional no qual os fatos ocorreram. Desse modo, será possível melhor compreender as variações das contas patrimoniais e de resultado que ocorreram ao longo dos anos de 2005 até 2015, tendo em vista o crescimento econômico brasileiro, a crise internacional de 2009, a recuperação da economia, e a crise política e recessão econômica que passou a vigorar no Brasil a partir do final de 2014
Keywords: PETROBRÁS; Análise econômico-financeira - 2005-2015; Indices; Ratio analysis